Studies on the phytoplankton of the deep subalpine Lake Iseo - Rosario MOSELLO (Journal of Limnology, 2003)
This paper reports the results of investigations carried out on the chemical characteristics and phytoplankton community of Lake Iseo. Samplings were performed on a monthly basis from 1998 to 2000. At least three main algal groups dominated the community throughout the study period. The large Bacillariophyceae were dominant mainly during late winter and early spring (Aulacoseira spp., Melosira varians, Asterionella formosa), with few species able to maintain occasional positive growth also during mid summer and/or autumn (Fragilaria crotonensis and Diatoma elongatum). The thermal stability of the water column and silica depletion were the main factors responsible for the decline of the large spring diatoms. The subsequent growth of Mougeotia sp. (Conjugatophyceae) was favoured by its lower sinking rate and resistance to increasing grazing pressure by the dominant copepods (Copidodiaptomus steueri) and cladocerans (Daphnia hyalina × galeata). Among the cyanobacteria, the greater development of Planktothrix rubescens in the autumn months, with conditions of vertical homogenisation and decreasing Zeu/Zmix ratios, was favoured by its ability to survive at low light irradiances. The temporal replacement of these three groups constitutes the main sequence of the annual phytoplankton succession in Lake Iseo. A large development of other algal groups was recorded only in one or two of the three study years (e.g. Dinophyceae and Chlorococcales). The changes observed in the annual phytoplankton development are discussed in the light of differences in the spring fertilisation of the waters, caused by differences in the depth of the layer involved in the late winter and spring vertical mixing.